2014
DOI: 10.12980/apjtb.4.2014c1312
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antileishmanial, antimalarial and antimicrobial metabolites from Jatropha multifida

Abstract: The research lends support to the ethnomedicinal use of the plant in combating microbial infections, leishmaniasis and malarial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
22
0
2
Order By: Relevance
“…A clerodane diterpene in L. donovani exhibited caspase-3/-7-like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stressmediated apoptotic cell death (Kathuria et al, 2014), while kaurenoic acid triggered the NLRP12/IL-1β/ cNOS/NO mechanism in Leishmania amazonensis (Miranda et al, 2015). A number of promising leishmicidal diterpenes have been reported (Sinha et al, 2000;Sairafianpour et al, 2001;Lala et al, 2003;Habtemariam, 2003;González et al, 2005;Fokialakis et al, 2006;Brito et al, 2006;Suryawanshi et al, 2008;Roy et al, 2010;Dos Santos et al, 2011;Mondal et al, 2013;Soares et al, 2013;Santos et al, 2013;Mothana et al, 2014;Moreira et al, 2014;Mokoka et al, 2014;Falodun et al, 2014;Demarchi et al, 2015;da Silva et al, 2015;Mizuno et al, 2015;Lima et al, 2015; Leprosy. It is also known as Hansen's disease, a longterm infection caused by the bacteria Mycobacterium leprae and Mycobacterium lepromatosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clerodane diterpene in L. donovani exhibited caspase-3/-7-like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stressmediated apoptotic cell death (Kathuria et al, 2014), while kaurenoic acid triggered the NLRP12/IL-1β/ cNOS/NO mechanism in Leishmania amazonensis (Miranda et al, 2015). A number of promising leishmicidal diterpenes have been reported (Sinha et al, 2000;Sairafianpour et al, 2001;Lala et al, 2003;Habtemariam, 2003;González et al, 2005;Fokialakis et al, 2006;Brito et al, 2006;Suryawanshi et al, 2008;Roy et al, 2010;Dos Santos et al, 2011;Mondal et al, 2013;Soares et al, 2013;Santos et al, 2013;Mothana et al, 2014;Moreira et al, 2014;Mokoka et al, 2014;Falodun et al, 2014;Demarchi et al, 2015;da Silva et al, 2015;Mizuno et al, 2015;Lima et al, 2015; Leprosy. It is also known as Hansen's disease, a longterm infection caused by the bacteria Mycobacterium leprae and Mycobacterium lepromatosis.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, diterpenes in nanoformulations (Roy et al, 2010;Mondal et al, 2013) as well as their laboratory derivatives have been reported to exhibit promising anti-NTDs activities (Watson and Preedy, 2010;Mander and Liu, 2010). Additionally, a number of diterpenes have been reported to act against multiple strains responsible for a particular NTD (Sanchez et al, 2006;Dea-Ayuela et al, 2016;Johnson et al, 1993;Riel et al, 2002;Clarkson et al, 2003;Kalauni et al, 2006;Ojo-Amaize et al, 2007;Wangchuk et al, 2010;González et al, 2014;Namukobe et al, 2015;Liu et al, 1997;Prabu et al, 2015;Encarnación-Dimayuga et al, 2006;Rijo et al, 2010;Arai et al, 2014;Xu et al, 2014a;Xu et al, 2014b) and NTDs (Schmidt et al, 2011;Al Musayeib et al, 2014;Ramírez-Macías et al, 2012;Mothana et al, 2014;Falodun et al, 2014;Mizuno et al, 2015;Mongkolvisut and Sutthivaiyakit, 2007;Rangkaew et al, 2009;Ospina and Rodríguez, 2009;Lekphrom et al, 2010;Almutairi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the human race, especially from developing countries depend on the traditional system of medicine for the management of various diseases. 1 Thousands of plant species are used medicinally, chiefly as herbal preparations in the indigenous systems of medicine in different countries and are sources of safe, cheap and potent drugs which have continued to be effective, successful, popular and modern chemistry has not been able to substitute a good number of them 1 .Plants are natural reservoirs of medicinal agents which are widely assumed to be safe, but many are potentially toxic. 2 In spite of the millions of chemical compounds currently synthesized in the laboratory, and available for screening for the action of therapeutic value, natural products, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids of JML [46,47] or PIW [48] are potential for the conductive organic polymer. Initially, the conductive polymer is in/below the semiconductor range after oxidizing or reducing process [49].…”
Section: The Influence Of Agnps On Crystal Size and Conductivity Of Jmentioning
confidence: 99%